Harmful Algal Blooms (HAB) in a changing world : the case of S and W Iberian Bays - Santos, Mariana Santinho Vieira dos (2022)
This thesis aimed to investigate, in two wide-open sheltered bays (Lisbon and Lagos) influenced by upwelling, how the meteorological and oceanographic (MetOc) setting may affect phytoplankton communities. Results of a 9-year time series data showed a high interannual variability of phytoplankton biomass, estimated as chlorophyll a (Chl-a). Nevertheless, the Chl-a sinusoidal model showed different temporal variability patterns in each bay: a uni-modal pattern with a short peak and low Chl-a concentrations in Lagos, and a weak bi-modal pattern with a long period of high Chl-a concentrations in Lisbon. Cross-correlation analyses performed for Chl-a and different MetOc variables indicated that PAR contributed most to Chl-a in winter/early-spring, while upwelling and SST were the main drivers in late-spring/summer. Analysis performed during 1-year showed significant spatial differences in phytoplankton assemblages between the bays. On a temporal scale, significant differences were observed on phytoplankton communities in both bays in the 4-meteorological seasons. However, results from a nearshore station studied in Lagos only indicated the occurrence of 3-biological seasons, with no significant differences between summer and autumn communities. This study suggests that Lagos region has a higher probability for the occurrence of HABs (in higher cell concentrations and persistence). The ecology of the benthic genus Ostreopsis was studied based on 7-years of water samples. Two species were identified reaching maximum cell densities in late-summer/early-autumn: Ostreopsis cf. ovata restricted to the south coast and Ostreopsis cf. siamensis present in both Portuguese coasts. Ostreopsis was much more abundant in Lagos (nearshore) and maxima concentrations were related to positive SST anomalies. High densities in the plankton were often recorded after a period of more than 2-weeks of low sea state, followed by short-time events of onshore wind and moderate waves. In Lisbon, O. cf. siamensis was seldom recorded in the plankton and no clear relationship could be established with the studied MetOc drivers. The recent records of Ostreopsis in this bay are interpreted as an early colonization stage of an invasion process. The present work highlights the relevance of the peculiarities of regional setting in determining phytoplankton dynamics in wide-open coastal bays influenced by upwelling, even at short latitudinal distance.